Evaluación de la efectividad del acaricida nimidane en el control de Boophilus microplus - Betancourt Echeverri, Jesús Antonio; Parra G., Danilo; Angel Arias, Carlos Eduardo (Instituto Colombiano Agropecuario - ICA, 2019)
In both, field and laboratory experiments conducted at MonterIa, Colombia, the product American Cyanamid Nimidane (Irnidocarbonic acid, (4 -Chloro-o-tolyl) -Dithio-, Ciclic methylene ester) showed to be efficient of for the control of Boophilus inicroplus. In naturally infested cattle, the adult tick population was reduced 92.6%, 2 days following spray treatment with a solution containing 500 ppm of the active principle. By day 19 post-treatment the reductio'n in adult ticks reached 993%. Engorged females expossed to the same concentration laid 87.9% less eggs than untreated control ticks. The acaricide showed a residual effect close to 8 days and a larvicidal effect - (based in motility of 100%).